Comparative Study of Linezolid and Vancomycin Regimens in One-Stage Surgery for Treating Limb Traumatic Osteomyelitis Caused by Methicillin-Resistant Staphylococcus aureus - Zhou Rongchang; Huang Kai; Guo Qiaofeng; Lin Bingyuan; Ren Haiyong; Liu Yiyang; Song Hongu (Polish Journal of Microbiology, 2023)
To compare the clinical outcomes of linezolid and vancomycin regimens combined with one-stage surgery in treating traumatic osteomyelitis of the limbs caused by methicillin-resistant Staphylococcus aureus (MRSA) infection. A retrospective study was performed to analyze patients with traumatic osteomyelitis of the limbs attributable to MRSA infection. All of these patients received one-stage surgery to debride their wounds, with subsequent implantation of a vancomycin-loaded calcium sulfate artificial bone. Patients received either intravenous linezolid (study group) or vancomycin (control group) during the perioperative period. The postoperative inflammatory markers, renal function, duration of drainage catheter placement, duration of antibiotic administration, length of hospital stay, adverse events, and recurrence of osteomyelitis in these two groups were compared. The study group had a shorter duration of antibiotic administration and length of hospital stay (p < 0.05). There was a significant difference in the incidences of adverse events between the two groups (5.88% and 17.65% in the study and control groups, respectively, p < 0.05). There was no recurrence in either group during the three-year follow-up period. As of year, five after the surgery, one patient in the control group had a recurrence of osteomyelitis. The linezolid regimen should be preferred to the vancomycin regimen in patients with traumatic osteomyelitis of the extremities caused by MRSA infection because the linezolid regimen showed fewer adverse events, shorter periods of antibiotic use, and shorter hospital stay. However, both treatment regimens achieved satisfactory outcomes and warranted further investigations.